On the Interaction of Surfactants with Gallium‐Based Liquid Metals. Issue 39 (18th October 2021) - Handschuh‐Wang, Stephan; Rauf, Muhammad; Gan, Tiansheng; Shang, Wenhui; Zhou, Xuechang
Abstract: Liquid metals have aroused interest in the scientific communities of electronics, engineering and biomedicine. In particular, the stabilization of liquid metal nanodroplets by surfactants and macromolecules has been investigated in the past extensively. Herein, we investigate the change in interfacial tension of the liquid metal Galinstan in contact with aqueous electrolytes upon addition of surfactants in aqueous solutions. We show that is governed by the chemical environment, the structure of the electric double layer (EDL) and the surfactant charge. In most environments a critical micelle concentration (CMC) can be determined, the value of which is in favorable agreement with literature values. Furthermore, based on the selective adsorption of the surfactant, the structure of the EDL is predicted and discussed, and the adsorption of surfactants is employed to mitigate liquid metal droplet coalescence. In this regard, the data suggests that the packing parameter, change in IFT upon surfactant addition and charge density of EDL are the main contributors for liquid metal droplet stability. Abstract : Measurement of the interfacial tension (IFT) was leveraged to measure the critical micelle concentration (CMC) and predict the structure of the electric double layer (EDL). From the IFT measurements and the stability of the liquid metal droplets versus droplet coalescence, the main contributing parameters for mitigating droplet coalescence were identified as the packing parameter, change in IFT upon surfactant addition and charge density of EDL are the main contributors for liquid metal droplet stability.